Global Distribution and Evolutionary History of Enterovirus D68, with Emphasis on the 2014 Outbreak in Ontario, Canada - Eshaghi, Alireza; Duvvuri, Venkata R.; Isabel, Sandra; Banh, Philip; Li, Aimin; Peci, Adriana; Patel, Samir N.; Gubbay, Jonathan B. (Frontiers in Microbiology, 2017)
Despite its first appearance in 1962, human enterovirus D68 (EV-D68) has been recognised as an emerging respiratory pathogen in the last decade when it caused outbreaks and clusters in several countries including Japan, the Philippines, and the Netherlands. The most recent and largest outbreak of EV-D68 associated with severe respiratory illness took place in North America between August 2014 and January 2015. Between September 1 and October 31 2014, , EV-D68 infection was laboratory confirmed among 153/907 (16.9%) persons tested for the virus at Public Health Ontario Laboratory, Canada, using real time RT-PCR and subsequent genotypingby sequencing of partial VP1 gene . In order to understand the evolutionary history of the 2014 North American EV-D68 outbreak, we conducted phylogenetic and phylodynamic analyses using available partial VP1 genes (n=469) and NCBI available whole genome sequences (WGS) (n=38). The global EV-D68 phylogenetic tree (n=469) reconfirms the divergence of three distinct clades A, B and C from the prototype EV-D68 Fermon strain as previously documented. Two sub-clades (B1 & B2) were identified, with most 2014 EV-D68 outbreak strains belonging to sub-cluster B2b2 (one of the two emerging clusters within sub-clade B2), with two signature substitutions T650A and M700V in BC and DE loops of VP1 gene, respectively. The close homology between WGS of strains from Ontario (n=2) and USA (n=21) in the recent EV-D68 outbreak suggests genetic relatedness and also a common source for the outbreak. The time of most recent common ancestor of EV-D68 and the 2014 EV-D68 outbreak strain suggest that the viruses possibly emerged during 1960-1961 and 2012-2013, respectively. We observed lower mean evolutionary rates of global EV-D68 using WGS data than estimated with partial VP1 gene sequences. Based on WGS data, the estimated mean rate of evolution of the EV-D68 B2b cluster was 9.75 x 10-3substitutions/site/year (95% BCI 4.11 x 10-3 to 16 x 10-3).